Modelo para la elaboración del informe final de autoevaluación con fines de acreditación del programa de Ingeniería Industrial de la Universidad de la Costa CUC. (2012)
The production of the final report of autoevaluation with ends of accreditation that allows to identify the reasons of every factor and characteristics contemplated in the CNA established in the University of the Coast CUC, the capture of actions in favor of the constant improvement of the processes of the Institution and to be able to state the influence that this phenomenon has and this way implement strategies, plans of work and East knowledge is basic and indispensable to be able to take decisions and undertake corrective effective actions. This Process of Production of the Report of the results of the Autoevaluation carries out applying a Scale of Equivalence, which helps us to determine the Percentage of fulfillment that has the factors and qualit characteristics, which leads us to determining a Degree of Acceptability and to act with a Strategy of Improvement for the above mentioned Characteristic for, already be, To increase, To promote, To strengthen or To support the quality, allowing to detect opportunities and the accomplishment of the feedback originating a new plan of improvement.